Intravital Multiphoton Microscopy as a Tool for Studying Renal Physiology, Pathophysiology and Therapeutics - Molitoris, Bruce A.; Sandoval, Ruben M.; Wagner, Mark C. (Frontiers in Physiology, 2022)
Intravital multiphoton microscopy has empowered investigators to quantitatively study dynamic cell and subcellular processes in vivo within normal and disease organs. Supportive advances in hardware, software, optics, transgenics and fluorescent probe design and development have together enabled new approaches to create a disruptive technology pioneering advances in understanding of normal biology, disease pathophysiology and therapies. Offering superior spatial and temporal resolution with high sensitivity, investigators can follow multiple processes simultaneously and observe complex interactions between different cell types, intracellular organelles, proteins and track molecules for cellular uptake, intracellular trafficking, and metabolism in a cell specific fashion. The technique has been utilized in the kidney to quantify multiple dynamic processes including capillary flow, permeability, glomerular function, proximal tubule processes and determine the effects of diseases and therapeutic mechanisms. Limitations include the depth of tissue penetration which is only about 100 microns. Tissue clearing technology has virtually eliminated penetration issues for fixed tissue studies. Use of multiphoton microscopy in preclinical animal models offers distinct advantages resulting in new insights into physiologic processes and the pathophysiology and treatment of diseases.